Feeding mechanisms of adult tropical horseshoe crab, Tachypleus gigas toward Feeds' conditions - Md Razak, Mohd Razali; Kassim, Zaleha (Akademi Sains Malaysia, 2018)
Information on feeding behaviour of tropical horseshoe crabs, Tachypleus gigas (M¨uller, 1785) is still scanty compared to Limulus polyphemus (Linnaeus, 1758). Foods condition such as decayed, sheltered and etc., would substantially influence the edibility of food by the T. gigas. However, horseshoe crabs might have specific behaviour to manipulate the foraged food. The aim of this paper was to investigate the feeding mechanism of T. gigas toward different feed conditions. Experiments were conducted inside a glass tank. A total of 30 males and females respectively were introduced to five different natural potential feeds, namely, gastropods (Turritella sp.), crustacean (Squilla sp.), fish (Lates calcarifer ), bivalve (Meretrix meretrix ) and polychaete (Nereis sp.). We have manipulated the condition of introduced feed based on the several potential foods conditions in nature such as sheltered (protected with shell, hard outer skin or host tube), unsheltered and decayed before introduced the feeds to the crabs. In present study, female crabs took shorter response period towards surrounding feed compared to males. Overall, they prefer to consume freshly dead feeds and would totally reject the sheltered feeds, such as, shell, hard outer skin and tube host. Male crabs have particular feeding behaviours to manipulate the edibility of the decayed feeds. Detailed experiments on the feeding mechanism of T. gigas could provide more information on their foraging activity in the wild.